Real exchange rate forecasting: a calibrated half-life PPP model can beat the random walk - Michele Ca' Zorzi; Jakub Muck; Michał Rubaszek (European Central Bank (ECB), 2013)
This paper brings three new insights into the Purchasing Power Parity (PPP) debate. First, we show that a half-life PPP model is able to forecast real exchange rates (RER) better than the random walk (RW) model at both short and long-term horizons. Secondly, we find that this result holds only if the speed of adjustment to the sample mean is calibrated at reasonable values rather than estimated. Finally, we find that it is also preferable to calibrate, rather than to elicit as a prior, the parameter determining the speed of adjustment to PPP.
Keywords: C32; F31; F37; 330; Exchange rate forecasting; half-life; purchasing power parity